Interactive jigsaw puzzle using backtracking algorithm / Amizah Mohd Kamaruzaman - Mohd Kamaruzaman, Amizah (2012)
Jigsaw puzzle games have been proved to help players develop the formation of the brain and also give fun to the player. Besides that, having a jigsaw puzzle game can help add more value to a website by bringing in the element offun. The Interactive Jigsaw Puzzle Using Backtracking Algorithm have been developed to be put on UiTM Terengganu’s website to attract more visitors to visit the website and at the same time to ensure recurring visitors. The objective of this project is to study the various techniques to develop online jigsaw puzzle games. Based on the initial study, the Backtracking algorithm has been chosen as the most suitable algorithm to be used to develop the jigsaw puzzle according to available time and complexity of the algorithm. The developed jigsaw puzzle was then tested to see the effectiveness ofthe Backtracking algorithm. This project followed the System Development Life Cycle (SDLC) model for the developing of the system. SDLC consists of analysis, design, implementation, testing and documentation phase. Backtracking algorithm are implemented in the implementation phase. After testing the developed jigsaw puzzle by comparing the result with automatic jigsaw puzzle solver using Backtracking algorithm, it shows that Backtracking algorithm are not suitable algorithm to be used to develop the interactive jigsaw puzzle because it takes longer time in solving the game as compared to Backtracking algorithm that used in automatic jigsaw puzzle solver that was found in previous research.